2019
DOI: 10.1029/2019gl082108
|View full text |Cite
|
Sign up to set email alerts
|

Role of the South Pacific Convergence Zone in West Antarctic Decadal Climate Variability

Abstract: Regional atmospheric circulation along coastal West Antarctica associated with the Amundsen Sea Low (ASL) mediates ice shelf melt that governs Antarctica's contribution to global sea level rise. In this study, the South Pacific Convergence Zone (SPCZ) is identified as a significant driver of ASL variability on decadal time scales. Using the Community Earth System Model, we impose a positive sea surface temperature anomaly in the SPCZ that reproduces an increase in convective rainfall in the southwest SPCZ that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 52 publications
6
29
5
Order By: Relevance
“…4d and 8a), the jet experiences an intensification in the South Pacific with a deepened Amundsen Sea low (ASL), compared to the poleward movement in the South Atlantic and southern Indian Ocean basins. While previous studies have suggested that the negative IPO could largely explain the deepened ASL in the austral cool seasons, through an anomalous stationary Rossby wave response, similar analysis for the austral summer season leads to a weakened ASL, opposite to that observed (Meehl et al 2016;Clem et al 2019). Therefore, further work is needed to understand the zonally asymmetric jet strengthening in the South Pacific basin.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4d and 8a), the jet experiences an intensification in the South Pacific with a deepened Amundsen Sea low (ASL), compared to the poleward movement in the South Atlantic and southern Indian Ocean basins. While previous studies have suggested that the negative IPO could largely explain the deepened ASL in the austral cool seasons, through an anomalous stationary Rossby wave response, similar analysis for the austral summer season leads to a weakened ASL, opposite to that observed (Meehl et al 2016;Clem et al 2019). Therefore, further work is needed to understand the zonally asymmetric jet strengthening in the South Pacific basin.…”
Section: Discussionmentioning
confidence: 87%
“…Some research has related the interdecadal Pacific oscillation (IPO) transition in the late 1990s to Antarctic climate variability. For example, the negative phase of the IPO has been linked to Antarctic sea ice expansion via a positive phase of the SAM combined with a deepened Amundsen Sea low (ASL), which alters the wind patterns over the Antarctic sea ice zone (Meehl et al 2016;Purich et al 2016;Clem et al 2019;Holland et al 2019;Meehl et al 2019b). Recent studies have also highlighted the role of Atlantic and Indian Ocean SSTs on Antarctic climate.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long-term warming trend, recent studies also show the existence of a regional cooling trend in some parts of Antarctica, including the Antarctic Peninsula, since the late 1990s (Carrasco, 2013;Turner et al, 2016;Oliva et al, 2017). However, this recent cooling period on the peninsula does not yet represent a shift in the overall robust warming trend, and is instead attributed to internal climate variability Gonzalez and Fortuny, 2018;Clem et al, 2019;Jones et al, 2019). The persistent windward warming trend in the autumn season as well as at the annual time scale during the recent cooling period could lead to important implications for the fate of ice sheet surfaces on the windward coasts.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The South Pacific Convergence Zone (SPCZ), a convective cloud band stretching from the Western Pacific Warm Pool toward French Polynesia (Trenberth, 1976; D. G. Vincent, 1994), is the largest rain band in the world during austral summer (December–February). The extensive and pervasive nature of this climate feature means the SPCZ plays a major role in South Pacific cyclogenesis and rainfall (E. M. Vincent et al, 2011) and a significant role in global‐scale circulation (D. G. Vincent, 1994), influencing the ocean freshwater budget, cross‐equatorial flow (Lorrey et al, 2012; Matthews, 2012), and circulation patterns across the southern oceans (Clem et al, 2019; Clem & Renwick, 2015). The presence and northwest‐southeast orientation of the SPCZ is controlled by underlying sea surface temperature (SST) gradients (van der Wiel et al, 2016; Widlansky et al, 2011), which determine the near‐surface wind conditions that result in low‐level moisture convergence (Ganachaud, 2014).…”
Section: Introductionmentioning
confidence: 99%